"I get knocked down but I get up again": Integrative frameworks for studying the development of motivational resilience in school. (July 2020) - Skinner, Ellen A.; Graham, Jennifer Pitzer; Brule, Heather; Rickert, Nicolette; Kindermann, Thomas A.
Many subareas share a common interest in students' motivational resilience, defined broadly as patterns of action that allow students to constructively deal with, overcome, recover, and learn from encounters with academic obstacles and failures. However, research in each of these areas often progresses in relative isolation, and studies rarely utilize developmental or social-contextual approaches. As a result, we do not yet have a clear understanding of how to help children and adolescents develop a rich and flexible repertoire of tools to deal productively with everyday academic challenges and difficulties. In this article, we knit together these disparate areas of work to create an integrated developmental and social-contextual framework that can guide the future study of these processes. First, we summarize nine areas of work that focus on students' actions on the ground when they encounter academic difficulties: academic resilience, mastery versus helplessness, engagement and re-engagement, academic coping, self-regulated learning, adaptive help seeking, emotion regulation, and buoyancy as well as tenacity, perseverance, and productive persistence. In each area, we highlight work that is explicitly developmental and that depicts key social-contextual factors that shape motivational resilience. Second, we sketch an overarching social-contextual and developmental framework that holds a place for each of these processes. Third, we identify multiple areas where cross-fertilization among researchers can contribute to improved educational practice and study of the development of motivational resilience. An overarching goal of this article (and the special section more generally) is to take first steps toward "field building" on this crucial topic.